Generation and characterization of a mouse line for monitoring translation in dopaminergic neurons - Joseph D. Dougherty (Nature Portfolio, 2017)
Abstract We developed a mouse line targeting midbrain dopamine neurons for Translating Ribosome Affinity Purification(TRAP). Here, we briefly report on the basic characterization of this mouse line including confirmation of expression of the transgene in midbrain dopamine neurons and validation of its effectiveness in capturing mRNA from these cells. We also report a translational profile of these neurons which may be of use to investigators studying the gene expression of these cells. Finally, we have provided the line to Jackson Laboratories for distribution and use in future studies.